Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1186/1550-2783-7-33
|View full text |Cite
|
Sign up to set email alerts
|

Sodium bicarbonate supplementation prevents skilled tennis performance decline after a simulated match

Abstract: The supplementation of sodium bicarbonate (NaHCO3) could increase performance or delay fatigue in intermittent high-intensity exercise. Prolonged tennis matches result in fatigue, which impairs skilled performance. The aim of this study was to investigate the effect of NaHCO3 supplementation on skilled tennis performance after a simulated match. Nine male college tennis players were recruited for this randomized cross-over, placebo-controlled, double-blind study. The participants consumed NaHCO3 (0.3 g. kg-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 46 publications
(66 reference statements)
4
39
0
Order By: Relevance
“…Interestingly, previous research10 25 found that the reductions in serve and groundstroke velocity were not necessarily accompanied by concomitant decreases in accuracy. More specifically, selective decreases in groundstroke (≈70%) and serve (≈30%) accuracy were evident following the Loughborough Intermittent Tennis Test,18 which superficially agrees with the reductions observed in stroke accuracy within other simulated or training environments 40 41. Despite this agreement, on deeper investigation, few studies show similarities in the reported type and extent of stroke accuracy reductions.…”
Section: Introductionsupporting
confidence: 58%
“…Interestingly, previous research10 25 found that the reductions in serve and groundstroke velocity were not necessarily accompanied by concomitant decreases in accuracy. More specifically, selective decreases in groundstroke (≈70%) and serve (≈30%) accuracy were evident following the Loughborough Intermittent Tennis Test,18 which superficially agrees with the reductions observed in stroke accuracy within other simulated or training environments 40 41. Despite this agreement, on deeper investigation, few studies show similarities in the reported type and extent of stroke accuracy reductions.…”
Section: Introductionsupporting
confidence: 58%
“…At the moderate‐intensity fatigue in which the heart rate was similar to that reported in real match play, the groundstroke accuracy was maintained in both expert and non‐expert players (Lyons et al., ). Furthermore, the accuracy scores of service and forehand groundstroke were unchanged after a simulated match (Wu et al., ). On the other hand, several studies did reveal the declines in skill performance.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies did reveal the declines in skill performance. The groundstroke accuracy was deteriorated (Hornery et al., , b, c), while the service and forehand groundstroke consistency scores were significantly decreased after a simulated match (Wu et al., ). These results indicated that, although there is evidence for neuromuscular fatigue after prolonged tennis play (Hornery et al., , b, c), experienced players can generally maintain the racquet control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies, which investigated NaHCO 3 ingestion during tournament-like sports, but only for single events. For example, it was shown that NaHCO 3 supplementation increases tennis performance [18] but does not affect prolonged intermittent cycling exercise performance [19]. However, up to date, no study investigated the effect of a consecutive multiday supplementation on consecutive multiday performance.…”
Section: Introductionmentioning
confidence: 99%